PENGARUH GREEN PRODUCT KNOWLEGDE, GREEN MARKETING, GREEN TRUST TERHADAP PURCHASE DECISIONS DENGAN GREEN PURCHASE INTENTION SEBAGAI VARIABEL INTERVENING PADA PEMBELIAN SEPADA MOTOR LISTRIK UWINFLY DI KABUPATEN PAMEKASAN - Angky Ayudia Ardena; Moh. Fajri; Moh Naufal Abror (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2026)
Global warming has become a major environmental issue worldwide. According to the Climate Transparency Report (2022), In Indonesia, the transportation sector is responsible for about 33% of the country’s total carbon emissions, with the majority originating from vehicles powered by fossil fuels. This condition has encouraged innovations in environmentally friendly transportation, such as electric motorcycles. This research examines how green product knowledge, green marketing, and green trust affect consumers’ intention to purchase Uwinfly electric motorcycles in Pamekasan Regency, Indonesia. A quantitative survey was conducted with 80 respondents from two official Uwinfly dealerships. The findings indicate that both green product knowledge and green marketing significantly and positively influence consumers’ intention to make green purchases, while green trust does not significantly influence it. Green product knowledge enhances consumers’ awareness of environmental and economic benefits, fostering sustainable consumption patterns. Green marketing strategies, including eco-friendly promotions and sustainability-focused branding, positively shape consumer interest and perceptions. The model explains 30.3% of the differences observed in green purchase intention, indicating that additional factors such as green brand image, environmental concern, and social influence may also contribute.